2022
DOI: 10.1108/cr-12-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Reporting on Sustainable Development Goals in the European Union: what drives companies’ decisions?

Abstract: Purpose This paper aims to identify the changes in the share of large public interest entities (PIEs) in European Union (EU) Member States providing Sustainable Development Goal (SDG) reporting prior to (2017) and after (2019) the implementation of Directive 2014/95/EU and the factors that influence their decisions to provide SDG reporting in 2019. Design/methodology/approach The authors use the multilevel theory of social change in organizations as the theoretical background. The sample consists of 341 PIEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…On the one hand, the first lens consists of the risk of SDGwashing, an emerging topic in accounting research. The attempt made by companies to disclose information about SDGs has been characterised by an intense debate about the reliability of this information (Krasodomska et al, 2023;Van Zanten et al, 2021). However, on the other hand, the negative impacts related to the provision of projects about SDGs could be explained by the physiological difficulty of representing the contribution provided by companies to the global goals identified by the 2030 Agenda (Pizzi et al, 2021a, b, c;Tsalis et al, 2020).…”
Section: Correlation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the first lens consists of the risk of SDGwashing, an emerging topic in accounting research. The attempt made by companies to disclose information about SDGs has been characterised by an intense debate about the reliability of this information (Krasodomska et al, 2023;Van Zanten et al, 2021). However, on the other hand, the negative impacts related to the provision of projects about SDGs could be explained by the physiological difficulty of representing the contribution provided by companies to the global goals identified by the 2030 Agenda (Pizzi et al, 2021a, b, c;Tsalis et al, 2020).…”
Section: Correlation Resultsmentioning
confidence: 99%
“…On the one hand, the first lens consists of the risk of SDG-washing, an emerging topic in accounting research. The attempt made by companies to disclose information about SDGs has been characterised by an intense debate about the reliability of this information (Krasodomska et al. , 2023; Van Zanten et al.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the last few years have also been characterized by the increasing adoption of methodological approaches based on the self-selection of indicators to assess sustainability reports' quality (Helfaya and Whittington, 2019). Those studies highlighted relevant differences between reports prepared according to specific legal requirements or reporting standards (Krasodomska et al, 2023;Pizzi et al, 2021). Thus, adopting reliable scoring systems could favor a more effective evaluation of the effects related to the disclosure of sustainability reporting.…”
Section: Analysts' Forecast Accuracymentioning
confidence: 99%
“…The results show that there is a high degree of correlation between the S&P and DJ indices and their relative sustainability indexes over the entire sample (December 1, 2012 to December 8, 2021) before and during the Covid-19 pandemic. Krasodomska et al (2022) study aims to identify changes in the share of large Public Interest Entities in European Union member states that submit Sustainable Development Goals (SDG) reports and the factors that influence their decisions to submit SDG reports. The results of the study showed that there is a significant positive change in the share of companies providing reference to the SDG in 2019 compared with 2017.…”
Section: Lecturer and Special Issue Reviewmentioning
confidence: 99%